A Study to Compare the Influential Factors of Contact Lens Discomfort in First -Time Soft Contact Lens Wearers - Sailaja, Kalla; Thakur, Renu; Sarika, Putta Vamsi (Journal of Neonatal Surgery, 2025)
Background: Contact lens discomfort (CLD) remains a predominant reason for contact lens dropout globally, despite advancements in lens materials and designs. The multifactorial nature of CLD—including ocular surface changes, dry eye symptoms, and visual fatigue—demands comprehensive evaluation. Objective: This study aims to compare anterior ocular surface health and subjective symptom questionnaires among three groups of first-time soft contact lens users to identify key contributors to CLD and develop evidence-based strategies for its management. Methods: A prospective, experimental, and comparative study was conducted on 90 healthy contact lens neophytes (aged 18–30), divided into three equal groups using Omafilcon-B (hydrogel), Comfilcon-A, and Fanfilcon-A (both silicone hydrogels). Anterior segment health was assessed using the Efron grading scale, Schirmer’s test, Tear Break-Up Time (TBUT), and AS-OCT-based corneal epithelial thickness. Subjective symptoms were evaluated using the Ocular Surface Disease Index (OSDI) and Convergence Insufficiency Symptom Survey (CISS). Baseline (pre-contact lens wear) and Follow-up assessments(post contact lens wear) were done at at 1, 2, and 3 months respectively. Results: All groups showed a statistically significant reduction in Schirmer’s test scores and TBUT over time (p < 0.01), with Group 3 demonstrating the greatest decline. Efron grading indicated transient mild inflammation at 1 month, which resolved by month 3. Corneal epithelial thickness decreased significantly(statistically) in all groups (p < 0.001), most notably in Group 3. CISS scores indicated a notable increase in eye strain, especially in Groups 1 and 3. Group 2 showed comparatively better ocular surface stability and symptom control. Conclusion: CLD in neophyte soft lens users is multifactorial, with tear film instability,mild redness, dryness, corneal epithelial thinning, and visual fatigue as significant contributors. Silicone hydrogel lenses, especially Comfilcon-A, may offer better ocular surface compatibility. Early detection and individualized management protocols, integrating both objective and subjective assessments, are essential to reduce contact lens dropout rates and enhance user satisfaction.